Die Kritik am romantischen Ideal in E. T. A. Hoffmanns «Der goldene Topf» (Studia theodisca, 2013)
E. T. A. Hoffmann’s Der Goldene Topf portrays fantasy and the ideal of romantic aestheticism as utopian on a metafictional level. However, another possibility should be considered: the temporary contemplation within poetry compensates for the loss of belief in the poeticization of the world as conceived by Novalis. The artistic entity cannot immerse itself in the romantic ideal. Since the narrator becomes part of the story and a victim of his imagination, the narration presents a critical viewpoint of the concept of genius.